Pengaruh Kartu Prakerja Terhadap Angka Pengangguran Di Sumatera Barat - Rana, Rahma Mia; Israyeni, Israyeni (Universitas Negeri Padang, 2024)
This study aims to determine the effect of pre-employment cards on the unemployment rate in west sumatra. The data used in this research is cross section data in 2022. This research is a quantitative research with logistic regression analysis model. This research shows that the variables of pre employment cards, courses, education level, age, marital status and gender have a significant negative effect in West Sumatera, while the variable of household members has no significant effect on the unemployment rate in West Sumatra.